Creativity and market: qualitative analysis of marketing in visual art in Mexico (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
This research analyzes art marketing as a social and economic phenomenon, where symbolic, cultural, and commercial dimensions converge. The objective is to understand, using the Theory of Reasoned Action as a framework, how art is positioned in the Mexican market, what strategies artists use to promote their works, and how these practices affect the perception and consumption of art. Among the strategies studied are market knowledge, value perception, differentiation, advertising strategies, promotion, pricing, and marketing channels, among other sociodemographic topics of the visual artist. Using a qualitative approach, based on a bibliographic review and in-depth interviews with ten visual artists from different regions of Mexico, tensions between symbolic value and market value are identified, as well as the implementation of empirical marketing strategies and their effectiveness. It is concluded that art marketing must reconcile artistic authenticity with commercial dynamics, as well as motivate a connection between Mexicans and art, promoting its consumption and appreciation, and fostering its consumption and appreciation. proposing hybrid and ethical models appropriate to the market without sacrificing visual art.
Keywords: Creativity; Marketing; Art; Mexico